Oyster cooking practices in the United States-based restaurants—A survey - Razieh Sadat Mirmahdi; Razieh Farzad; Andrew J. MacIntosh; Arie H. Havelaar; Amarat H. Simonne; Naim Montazeri (PLoS ONE, 2025)
Despite longstanding oyster cooking recommendations, outbreaks associated with cooked oysters still occur. A survey of U.S.-based restaurants was conducted to investigate common cooking practices, including steaming, baking, and roasting. Target restaurants were identified using Standard Industrial Classification (SIC) codes and surveyed through live phone interviews and online. The questionnaire included open- and closed-ended questions for restaurant staff, including chefs and managers, with topics covering customer and serving quantities, source of purchase, common cooking methods, cooking time and temperature combinations, and the use of thermometers. A total of 105 complete responses were collected from California, Florida, Louisiana, Massachusetts, Oregon, Virginia, and Washington. On a weekly basis, the majority of restaurants served 1–1,000 customers with 1–500 dozen oysters. The most frequently used cooking methods were frying (46%), followed by baking (36%), steaming (30%), and then roasting (23%). On average, baking was performed at a temperature of 185 ± 64°C for 9 ± 4 minutes, roasting at 207 ± 54°C for 8 ± 6 minutes, and steaming for 5 ± 3 minutes, with no correlation being found between cooking time and temperature for either technique. Additionally, 57% of the surveyed restaurants did not use thermometers when cooking oysters. This study highlights the variations in oyster cooking practices in U.S. restaurants, emphasizing the need to assess the effectiveness of different cooking techniques through quantitative microbial risk assessment of the most common pathogens in oysters. This will help improve food safety guidelines and minimize health risks associated with the consumption of partially cooked oysters.